Caries detection with DIAGNOdent and ultrasound - TAĞTEKİN, DİLEK; YANIKOĞLU, FUNDA (MOSBY-ELSEVIER, 2008)
Objective. The objective of this study was to evaluate the repeatability of 2 nondestructive caries detection methods, ultrasound (ULS) and DIAGNOdent, for the detection of approximal caries lesions, and to evaluate 2 tips provided for the DIAGNOdent. Study design. White/brown-spot lesions (n = 42) were captured by a digital camera, and measured by test methods and confocal laser scanning microscope (CLSM). Intra- and inter-observer reliability, accuracy, and Cohen's kappa and Spearman's rho statistics were used. Results. At DIAGNOdent, intra-observer agreements were 78.5%, 66.7% for A tip and 59.5%, 47.6% for B for 2 examiners, respectively. Accuracy of both tips was 50% for the first examiner; 45.3% for A and 47.6% for the B tip for the second examiner. All ULS measurements were accurate, reliable, and positively and significantly correlated between examiners. Conclusion. The A tip of the DIAGNOdent was found to be better than the B tip for the detection of enamel caries. All DIAGNOdent and ULS measurements were positive and significantly correlated for both examiners. Both methods demonstrated high repeatability and accuracy. (Oral Surg Oral Med Oral Pathol Oral Radiol Endod 2008; 106: 729-35)
Keywords: LASER FLUORESCENCE SYSTEM; SMOOTH-SURFACE CARIES; IN-VITRO; OCCLUSAL CARIES; DEMINERALIZED ENAMEL; VISUAL EXAMINATION; LESIONS; TEETH; QUANTIFICATION; PERFORMANCE